STUDI SIFAT FISIK, KIMIA, FUNGSIONAL, DAN KADAR ASAM SIANIDA TEPUNG KECAMBAH KACANG KORO PEDANG (Canavalia ensiformis L.) - Damayanti, I Dewa Ayu Bintang; Wisaniyasa, Ni Wayan; Widarta, I Wayan Rai (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 3 (2019): Jurnal ITEPA, 2019)
The purpose of this research was to determine the physical, chemical, functional properties, and hydrogen cyanide content of jack bean sprout ( Canavalia ensiformis L.) flour. This research used two treatments that was without germination and 48 hours of germination. The treatments were repeated three times resulting in six units of experiments. Jack bean flour and jack bean sprout flour were analyzed by paired T-test. The results showed that the germination of jackbean had a very significant effect on the decrease of oil absorption from 1.59 mg/l to 0.79 mg/l. The treatment had a significant effect on the increase of water content from 11.10% to 11.77%; increase of protein content from 28.52% to 29.18%; decrease of fat content from 6.33% to 5.54%; decrease of carbohydrate content from 51.19% to 50.77%; increase of crude fiber content from 11.69% to 12.30%; increase of water holding capacity from 1.42 ml/g to 1.58 ml/g; decrease of swelling volume from 8.97 ml/g to 8.31 ml/g; increase of solubility from 0.06% to 0.07%; and decrease of hydrogen cyanide content from 14.13 mg/kg to 11.00 mg/kg. This research had no effect on bulk density and ash content.   Keywords       : hydrogen cyanide; jackbean sprout flour; chemical, functional and physical properties